Epi InfoTM a mHealth tool for primary field data collection in subsample population of Uttarakhand- A cross sectional study. - Aggarwal, Pradeep; Kakkar, Rakesh; Bijalwan, Rajiv; Kaur, Gagan Deep; Pandey, Vivek Kumar; Kumar, Santosh (Indian Journal of Community Health, 2016)
Background: A deficient data is among the biggest obstacle facing planners and policy makers. Health data collection in the developing world is often hampered by the high costs and inefficiencies of traditional large-scale paper-based surveys. mHealth using Epi-Info is most appropriate tool to create, share, deploy health surveys and for strengthening of health systems. The program runs on free and open software, is easy to use, and can be downloaded to handheld devices to be used by workers in the field. Objectives: To find out the usefulness and limitations of data collection for mHealth by use of Epi InfoTM software. Methods: The devices used Epi Info 7.1.5 (Android version), which has been modeled as a database with variables of the traditional form. A cross sectional survey among adolescents regarding their health needs was carried out in a sample of 200 adolescents (purposive sampling) of rural hilly (Jaunpur block of Tehri Garhwal district) and plain (Doiwala block of Dehradun district) areas of Uttarakhand by the use of Android tablets with Epi InfoTM. Results: It was found that adolescent questionnaire tool developed in Epi InfoTM android tablet application is a powerful tool for data collection having numerable practical advantages like: Interview Time Tracking (ITT) that gives the reality check in field studies along with cases Geographical presentation by GIS mapping. In addition to this complete filling of data in field so no left over or guessing for data entry operator, paperless, bio-friendly. Despite of Tablet cost, it is cost effective as tablet can be repeatedly used for other surveys. Conclusions: Epi InfoTM is a developing open access software for primary data collection and analyzing data from the field, with advantageous benefits of epidemiological surveys.